The role of repeat cerclage in managing subsequent pregnancies for patients with a prior history of cervical cerclage: a retrospective self-control study - Zhang, Lidan; Hu, Mengyang; Yang, Xiaofu; Zhao, Peng (Frontiers in Medicine, 2025)
In a woman who received cerclage in the previous pregnancy, obstetricians were highly likely to perform this surgery in her subsequent pregnancy. However, many researchers have advocated against the use of repeat cerclage. The objective of this study was to evaluate the effectiveness of repeat cerclage in managing the subsequent pregnancy for participants with a history of cervical cerclage. We retrospectively collected data from patients who had a history of cervical cerclage and received repeat cerclage in the subsequent pregnancy. A self-controlled comparative analysis was undertaken to evaluate the differences in baseline characteristics and pregnancy outcomes between the initial cerclage and the repeat cerclage. A total of 173 patients were included in the study. These patients were divided into two groups, the initial cerclage group and the repeat cerclage group. Consequently, the gestational age at delivery, birth weight, live birth outcome, and neonatal morbidity in the repeat cerclage group were significantly improved compared to the initial cerclage group (p < 0.001 for all aforementioned indicators). All patients were further divided into four subgroups based on their indications for initial cerclage. Specifically, 54 patients received an initial cerclage due to prior history (group A), 45 patients based on ultrasound findings (group B), 63 patients due to physical examination (group C), and 11 participants for inappropriate indications (group D). As a result, repeat cerclage significantly increased both gestational age at delivery and birth weight in group A, group B, and group C, with statistical significance noted as follows: group A (p = 0.007 for gestational age, p = 0.044 for birth weight), group B (p = 0.002 for gestational age, p = 0.011 for birth weight), and group C (p < 0.001 for both) No significant differences were noted in group D. In conclusion, the clinical outcome of repeat cerclage in patients with a prior history of cervical cerclage, regardless of whether it was indicated by history, ultrasound, or physical examination, was found to be significantly beneficial for the patients. For patients who have undergone a prior cerclage based on evidence-supported indications of CI, repeat cerclage may be a prudent consideration.